Edukasi Peningkatan Pengetahuan Tentang Penyakit Asma: Education to increase knowledge about asthma - Hapipah; Istianah (Jurnal Abdi Keperawatan dan Kedokteran, 2023)
Asthma is a disease that is often found in society and is a public problem throughout the world. The importance of asthma prevention efforts aims to prevent sufferers from experiencing a recurrence of their disease, thereby reducing visits to health services for treatment. This community service aims to increase public knowledge about asthma by providing education to the public. This community service activity was carried out using the lecture, discussion and demonstration method which was carried out on December 22 2022 in the Kumbak of Ranggagata village, Central Lombok with 51 participants to measure residents' knowledge about asthma. The instrument used in this community service activity is a knowledge questionnaire about asthma. Before being given education in the form of health counseling about asthma, participants were given a pre-test and after delivering the material, a post-test was carried out to observe the participants' knowledge. The results of the evaluation of this activity showed that the participants understood and understood asthma, the factors that trigger a relapse, how to prevent an asthma attack and were able to practice deep breathing relaxation therapy to reduce shortness of breath. The knowledge of the Kumbak hamlet residents before being given health counseling about asthma was mostly lacking, namely as many as 38 people (74.5%), increased after being given health education to a sufficient level of knowledge of 29 people (56.9%). There was an increase in the knowledge of the Kumbak hamlet community about asthma after health counseling was carried out. This community service activity is expected to be carried out on an ongoing basis to increase public knowledge about other health problems.